We make the future of youngsters. Mysterious disease threatens lives, a case of primary vesicoureteral reflux - Mohamed, Mossad Abdelhak Shaban; Mossad, Manar; Taher, Abdulbasit abdulhaleem; Muhd Helmi, Muhd Alwi (2021)
Vesicoureteral reflux (VUR) is the retrograde urine passage from the bladder into the upper urinary tract. Primary VUR occurs in approximately 1 per cent of newborns. Abnormalities are seen on ultrasound in 35 to 50 per cent of neonates and young infants less than three months of age with UTI. A 52-day male infant with no significant perinatal history other than birth weight 2.4kg was admitted to the hospital for the first time with three days of high-grade fever. He has no other symptoms, and systemic clinical examination was inconclusive. The investigations showed negative COVID19, Leukocytosis with predominant neutrophil, high CRP, microcytic hypochromic anaemia, average renal profile. The baby started on c-penicillin and gentamicin planned for urine and CSF analysis. The urine's microscopic exam was acceptable, and CSF analysis showed total WBC 8 neutrophils 8 with normal protein and glucose, as the baby started on cefotaxime awaiting culture results. After two days, the CSF culture was negative. However, urine culture came positive for E Coli. KUB ultrasound showed well-distended Urinary bladder, normal wall thickening, no bladder calculus, dilated Left ureter with dilated renal pelvis bilaterally diagnosis, Vesicoureteral reflux. Indicate contrast voiding cystourethrogram (VCUG) and dimercaptosuccinic acid (DMSA) renal scan confirmed the diagnosis and stage. The baby improved on IV antibiotics for seven days, followed by seven days oral, then prophylactic antibiotics awaiting long term follow up. A complete septic profile, including urine analysis, should be done in febrile neonates after six days of life unless other consideration. The relation between IUGR and associated kidney problems need further consideration. Lastly, VUR can cause recurrent acute pyelonephritis, leading to renal scarring, loss of renal tissue, hypertension, and end-stage renal disease.